2012
DOI: 10.1074/jbc.c112.387332
|View full text |Cite
|
Sign up to set email alerts
|

6′-Guanidinonaltrindole (6′-GNTI) Is a G Protein-biased κ-Opioid Receptor Agonist That Inhibits Arrestin Recruitment

Abstract: Background: Arrestin recruitment to the -opioid receptor (KOR) has been linked to several adverse effects of analgesics, such as dysphoria and tolerance. Results: We identified 6Ј-guanidinonaltrindole (6Ј-GNTI) as a potent KOR agonist for G protein activation that fails to recruit arrestin. Conclusion: 6Ј-GNTI is an extreme G protein-biased KOR ligand. Significance: 6Ј-GNTI is a lead toward analgesics with fewer arrestin-mediated adverse effects.-Opioid receptor (KOR) agonists do not activate the reward pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 36 publications
8
100
1
Order By: Relevance
“…Furthermore, the tested morphinans (Table 3) and benzomorphans (Table 4) tested displayed very little bias. Only 69-GNTI displayed a slight G protein bias (bias factor of 6), consistent with previous studies (Rives et al, 2012;Schmid et al, 2013). Also, we found that the antagonist JDTic has no agonistic activity in either G protein or arrestin assays (Table 4).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Furthermore, the tested morphinans (Table 3) and benzomorphans (Table 4) tested displayed very little bias. Only 69-GNTI displayed a slight G protein bias (bias factor of 6), consistent with previous studies (Rives et al, 2012;Schmid et al, 2013). Also, we found that the antagonist JDTic has no agonistic activity in either G protein or arrestin assays (Table 4).…”
Section: Resultssupporting
confidence: 79%
“…To confirm our results from the Tango arrestin recruitment assay, we used a BRET-based arrestin-recruitment assay (Rives et al, 2012) to further analyze the compounds displaying the highest degree of bias. Salvinorin A displayed very similar potency values for the Tango and BRET assays (5.56 and 5.63 nM, respectively) ( Tables 1 and 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be seen using 69-GNTI, which produces a clear and distinct activation of response in both assays that can easily be resolved from the baseline. Although the competitive model does not confer a distinct benefit over the standard model for 69-GNTI, both the standard and competitive methods provide estimates of 69-GNTI bias toward G protein signaling that are in agreement with previous studies (Rives et al, 2012;Schmid et al, 2013). In this case, the data obtained by calculating relative affinity using the competitive analysis does not further resolve the estimation of bias; moreover, this approach may actually introduce error into the analysis, as evidenced by an increase in the width of the 95% CIs.…”
Section: Discussionsupporting
confidence: 78%
“…For example, 69-guanidinonaltrindole (69-GNTI) was initially characterized as a potent partial KOR agonist (Sharma et al, 2001). It was subsequently shown to stimulate G protein coupling yet induced very little detectable barrestin2 recruitment when compared with U69,593 [(1)-(5a,7a,8b)-N-methyl-N-[7-(1-pyrrolidinyl)-1-oxaspiro[4.5]dec-8-yl]-benzeneacetamide], a KOR agonist that displays high efficacy in both assays (Rives et al, 2012;Schmid et al, 2013). Using the method of bias analysis described by Ehlert (2008) and Kenakin et al (2012), referred to herein as the "standard" model, 69-GNTI was determined to be a biased agonist for G protein signaling over barrestin2 recruitment .…”
Section: Introductionmentioning
confidence: 99%